KEDUDUKAN HARTA PERKAWINAN SETELAH PERCERAIAN DITINJAU DARI KOMPILASI HUKUM ISLAM - Iskandar Laka (Fakultas Hukum, Universitas Muhammadiyah Pontianak, 2019)
The definition of property in marriage according to Law Number 1 of 1974 concerning marriage is abbreviated (Law No. 1 Year 1974) in Article 35 states that the property obtained in marriage becomes a joint asset, while the subordinate assets of each husband or wife and property acquired by each husband or wife as a gift or inheritance under their respective supervision insofar as the parties do not determine otherwise. According to Article 37 of Law Number 1 Year 1974 concerning abbreviated marriage (Law No. 1 Year 1974), it is explained that: